Pengalaman Afektif Sebagai Mediator antara Penggunaan Media Sosial terhadap Alexithymia pada Mahasiswa di Pekanbaru - Ismi Nur Mawahdah Ihsani; Nurul Aiyuda; Itto Nesyia Nasution (Bandung Conference Series: Psychology Science, 2022)
Abstract. Alexithymia is referred to as 'emotional deafness', a condition in which individuals do not have the ability to understand their own feelings and those of others. Alexithymia is reinforced by technological developments, alexithymia is associated with excessive use of social media. The social media usage can lead to reduced ability to manage affective experiences when individuals tend to be more individualistic and have low socialization. When individuals do not have the ability to manage affective experiences well, it can cause alexithymia. This study aims to examine the mediating effect of social media use on alexithymia through affective experiences. This research is a quantitative research with mediation analysis. The research sample was 204 people (109 women) and 95 people (men) with an age range of 18 to 33 years. using the Quota Sampling sampling technique. The research data were taken using the affective experience scale, the social media use scale and the alexithymia scale. The results showed that affective experience can partially mediate the use of social media on alexithymia (partial mediation) with Value = 0.556 and p = 0.000. Abstrak. Alexithymia disebut sebagai ‘tuli emosional’, kondisi dimana individu tidak memiliki kemampuan untuk memahami perasaan diri sendiri dan perasaan orang lain. Alexithymia diperkuat dengan adanya perkembangan teknologi, alexithymia berhubungan dengan penggunaan media sosial secara berlebihan. Penggunaan media sosial dapat menyebabkan berkurangnya kemampuan mengelola pengalaman afektif ketika individu cenderung lebih individualis dan sosialisasi yang rendah. Ketika individu tidak memiliki kemampuan mengelola pengalaman afektif dengan baik dapat menyebabkan alexithymia. Penelitian ini bertujuan untuk melihat pengaruh mediasi penggunaan media sosial terhadap alexithymia melalui pengalaman afektif. Penelitian ini merupakan penelitian kuantitatif dengan analisis mediasi. Sampel penelitian berjumlah 204 orang (perempuan 109 orang) dan (laki-laki 95orang) dengan rentang usia 18 sampai dengan 33 tahun menggunakan teknik pengambilan sampel Quota Sampling. Data penelitian diambil menggunakan skala pengalaman afektif, skala penggunaan media sosial dan skala alexithymia. Hasil penelitian menunjukkan bahwa pengalaman afektif dapat memediasi penggunaan media sosial terhadap alexithymia secara partial (partial mediation) dengan Value= 0.556 dan p=0.000.